GEOPOLITICAL CONSEQUENCES OF BASHAR AL-ASSAD’S FALL IN SYRIA - Gajic, Aleksandar (The Policy of National Security, 2026)
Adhering to the theoretical framework of classical geopolitcal analysis, the paper provides a geopolitical overview of the change of government in Syria at the end of the prolonged civil war, as well as the course of military operations and a description of the immediately established new situation on the ground. The introductory part of the paper explains the basic weaknesses of the Bashar al-Assad regime, as well as its main flaws that caused its collapse in a period of only eleven days. The second segment of the paper explains the geopolitical importance of Syria in a historical perspective by pointing out its constants within the Levant as an intermediate space in the Middle East located between the areas occupied by regional geopolitical powers in different historical eras. In this way, the similarity between former and the current circumstances is pointed out. The middle part of the paper observes geopolitical dimensions of the newly established state, the ideological and political background of HTS, the ruling military faction in the new, Sunni government in Damascus, as well as its relationship with other factions and their strongholds in the certain areas within Syria. The third part of the paper analyses the influence of external great and regional powers on the situation in contemporary Syria and their interest projections which conflict each other in many ways. The final part of the paper deals with a prognostic assessment of the further geopolitical prospects of post-Assad Syria, taking into account the existing antagonisms and different interests of both Syrian military and ethnic formations and external powers.